Effects of ginseng supplementation on supramaximal exercise performance and short-term recovery - Engels, H.-J. (The Journal of Strength and Conditioning Research, 2001)
The purpose of this study was to examine the effects of long-term ginseng supplementation on short, supramaximal exercise performance and short-term recovery. Using a double-blind protocol, 24 healthy, active women were randomly assigned to a ginseng (n = 12) or placebo (n = 12) treatment group. Each participant added a standardized extract of Panax ginseng C.A. Meyer (400 mg per day of G115) or placebo to their normal diet for 8 weeks (56-60 days). Before and after the trial period, each subject performed an all-out-effort, 30-second leg cycle ergometry test (Wingate protocol) followed by a controlled recovery under constant laboratory conditions. Nineteen subjects completed the study. Analysis of variance using pretest to posttest change scores revealed no significant difference between the ginseng and placebo study groups for the following variables measured: peak anaerobic power output, mean anaerobic power output, rate of fatigue, and immediate postexercise recovery heart rates (p > 0.05). In conclusion, the present data indicate that prolonged supplementation with ginseng (P. ginseng C.A. Meyer) has no ergogenic benefits during and in the recovery from short, supramaximal exercise.